What can fuel price increases tell us about the air pollution health co-benefits of a carbon price?. (March 2018) - Shaw, Caroline; Hales, Simon; Edwards, Richard; Howden-Chapman, Philippa; Stanley, James
Abstract: Background: Despite their currency, there is little 'real-world' evidence for the health co-benefits of policies to reduce carbon dioxide emissions. Objectives: To explore whether increases in market petrol and diesel price have a discernible impact on ambient air pollution. Methods: A causal diagram informed the analysis. Linear regression was conducted on weekly air pollutant time-series (PM10, NOx, PM2.5 and CO) for four air quality monitoring stations around New Zealand, and diesel and petrol pricing data, from 2001 to 2013. We explored the possible delayed effects of petrol and diesel price changes over 9 weeks. Flexible cubic splines were used to remove seasonal and long-term trends. Meta-analysis of results from the four stations was undertaken, as were sensitivity analyses. Results: The unlagged adjusted models for each air quality station and the meta-analyses showed a modest, non-significant reduction in air pollutants (PM10, NOx, PM2.5 and CO) associated with an increase in petrol price. For example, a 1% increase in petrol price was associated with a 0.32% (−1.21 to 0.58) reduction in NOx . All confidence intervals included null. While the lagged adjusted models showed patterns suggestive of an initial drop in air pollutants after a fuel price rise, followed by a rebound increase over the nine-week period studied, the majority of estimates were non-significant. Conclusions: The findings are suggestive of a short-term reduction in air pollutants associated with regular petrol or diesel fuel price rises, followed by a rebound increase. Further work could explore the specific pathways between fuel price and air pollution. Highlights: This study examined the impact of fuel price changes on transport-related air pollutants (PM10, PM2.5, NO2 and CO). Study results suggest a short term reduction in air pollution after an increase in fuel price. Further work exploring specific pathways between fuel price and air pollution could be useful.